The use of historical photography in environmental studies - Peter Collier (Unité Mixte de Recherche 8504 Géographie-cités, 2001)
The time-scales over which significant environmental changes take place can vary from a few hours on highly mobile coastal sediments to tens or even hundreds of years on exposed stone surfaces. Studies of rapidly changing features can be carried out using traditional field monitoring techniques, perhaps aided by airborne or satellite imagery if the scale of change is sufficiently large. Less dynamic surfaces do not lend themselves to such methods since, over the time-scale of traditional research projects, the amount of change will be less than the known errors in the measurement techniques. This paper describes the use of historical aerial photographs to study changes in an inter-tidal environment, around Langstone Harbour and Chichester Harbour (U.K.), and discusses the advantages and limitations of this data source.